2007
DOI: 10.1016/j.bbabio.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of chlorophyll a/b-binding Pcb proteins with photosystems I and II in Prochlorothrix hollandica

Abstract: Action spectra for photosystem II (PSII)-driven oxygen evolution and of photosystem I (PSI)-mediated H(2) photoproduction and photoinhibition of respiration were used to determine the participation of chlorophyll (Chl) a/b-binding Pcb proteins in the functions of pigment apparatus of Prochlorothrix hollandica. Comparison of the in situ action spectra with absorption spectra of PSII and PSI complexes isolated from the cyanobacterium Synechocystis 6803 revealed a shoulder at 650 nm that indicated presence of Chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Photosynthetic action spectra measurements and determination of PSI to PSII ratios Polarographic measurements of the flash-induced gas exchange reactions related to photochemical activities of PSII (O 2 evolution) and PSI (photoinhibition of aerobic respiratory O 2 uptake) and their action spectra were performed as described in detail previously (Boichenko 2004;Boichenko et al 2007). A bare platinum electrode at a potential-0.7 V vs. Ag/AgCl reference electrode-was used to measure photoinduced O 2 gas exchange rate.…”
Section: Samples Preparationmentioning
confidence: 99%
“…Photosynthetic action spectra measurements and determination of PSI to PSII ratios Polarographic measurements of the flash-induced gas exchange reactions related to photochemical activities of PSII (O 2 evolution) and PSI (photoinhibition of aerobic respiratory O 2 uptake) and their action spectra were performed as described in detail previously (Boichenko 2004;Boichenko et al 2007). A bare platinum electrode at a potential-0.7 V vs. Ag/AgCl reference electrode-was used to measure photoinduced O 2 gas exchange rate.…”
Section: Samples Preparationmentioning
confidence: 99%
“…The antenna proteins pcbAB selectively associate with PSII, while the antenna protein PcbC is attached to PSI (Bumba et al, 2005). Photosystems I and II in P. hollandica have the peripheral antennae which produce a 18-meric ring around the PSI trimer and a 14-meric ring around the PSII dimer (Boichenko et al, 2007). Prochlorothrix hollandica is the only green cyanobacterium in which a shift of photosynthetic States 1 ↔ 2 (i.e., preferential light channeling) was demonstrated.…”
Section: Functional Ecologymentioning
confidence: 99%
“…Pcb proteins aggregate in multimeric super complexes (Bibby et al, 2001, 2003; Chen et al, 2002, 2005; Partensky and Garczarek, 2003) which surround the oligomers of PSI and PSII (Bibby et al, 2003; Boichenko et al, 2007). PcbA/PcbB proteins build up the mobile antenna of both photosystems, while the PcbC proteins associate with a portion of antenna tightly bound to PSI (Herbstová et al, 2010).…”
Section: Energy Assimilationmentioning
confidence: 99%
“…Three prochlorophyte genera have been described: Prochlorococcus, Prochlorothrix, and Prochloron (Lewin 2002). All of them use chlorophyll-binding protein complexes, named Pcb complexes, as their major light-harvesting components (Chen and Bibby 2005;Boichenko et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the availability of complete genomic information of a number of cyanobacteria has revealed that the Pcb-like proteins have a wider distribution than just prochlorophytes and often exhibit a unique arrangement of multiple copies (Garczarek et al 2000;Bibby et al 2003a, b;Bumba et al 2005;Chen and Bibby 2005;Boichenko et al 2007). It is now clear that Pcb-type complexes are not unique light-harvesting components that only exist in prochlorophytes, but are also found in classical cyanobacteria, such as Fischerella, Anabaena (Geiss et al 2001), and also in Acaryochloris (Chen et al 2005c).…”
Section: Introductionmentioning
confidence: 99%